External Quality Assurance for Laboratory Identification and Capsular Typing of Streptococcus pneumoniae. Issue 1 (December 2017) - Slotved, Hans-Christian; Sheppard, Carmen; Dalby, Tine; van der Ende, Arie; Fry, Norman; Morfeldt, Eva; Nyholm, Outi; Rokney, Assaf; Ron, Merav; Siira, Lotta; Scott, Kevin; Smith, Andrew; et al.
Abstract An external quality assessment (EQA) scheme for pneumococcal serotype identification has been performed over a period of 11 years, by a network of European pneumococcal reference laboratories. We report the results from the EQA, and present an assessment of the acceptability and utility of the EQA scheme. Reports from 22 EQA panels distributed in 2005–2016 were analysed. Each EQA panel consisted of seven isolates. A questionnaire including seven questions related to the acceptability and utility of the EQA scheme was distributed to all participating laboratories. Altogether, 154 pneumococcal isolates were tested. Of the 92 serologically distinct serotypes currently defined, 49 serotypes were included in the rounds. Discrepant results were observed in eight EQA rounds, involving 11 isolates (7.1%, 95% CI: 4% to 12%). All participating laboratories reported that the EQA scheme was useful for quality assurance purposes. Our results show that comparable serotyping data can be obtained in different laboratories. The EQA participation helps to keep the typing procedures at a high standard and provides data for accreditation purposes. The EQA is helpful when new technologies are introduced, and reveal limitations of both genotypic and phenotypic methods. Continuation of the presented EQA scheme is planned.